2020
DOI: 10.1038/s41598-020-63787-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential Pathogenic Bacteria in Seminal Microbiota of Patients with Different Types of Dysspermatism

Abstract: Human microbiota play an important role in the health of their human hosts. Recent studies have demonstrated that microbiota exist in seminal plasma. The current study aims to elucidate whether seminal microbiota exist in patients with different types of dysspermatism and whether bacterial biomarkers can be identified for them. A total of 159 study participants were recruited, including 22 patients with oligoasthenospermia, 58 patients with asthenospermia, 8 patients with azoospermia, 13 patients with oligospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 48 publications
8
66
1
2
Order By: Relevance
“…The same five dominant phyla were found as a part of microbiota in human seminal plasma: Proteobacteria, Firmicutes, Actinobacteria, Bacteroidetes and Fusobacteria [ 43 ]. This is also consistent with the findings of a previous study of the human testicular microbiome [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same five dominant phyla were found as a part of microbiota in human seminal plasma: Proteobacteria, Firmicutes, Actinobacteria, Bacteroidetes and Fusobacteria [ 43 ]. This is also consistent with the findings of a previous study of the human testicular microbiome [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we identified Prevotella in >90% of our testicular samples. Prevotella genus has been associated with low-quality semen when analysing semen samples from humans (Baud et al, 2019;Campisciano et al, 2020;Farahani et al, 2020;Jarvi et al, 1996;Nguyen et al, 2014;Weng et al, 2014;Yang et al, 2020), suggesting that species within Prevotella could contribute to the spermatogenesis defects and male infertility (Ding et al, 2020;Yang et al, 2020). The pioneering study of the testicular microbiome (Alfano et al, 2018) did not present their results on bacterial genus level and, therefore, our study results on specific testicular bacteria are not comparable, while on phylum level our identified phyla were also reported in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant microbial genera detected in dispermic patients and healthy donors are Lactobacillus, Pseudomonas, Prevotella and Proteobacteria, Firmicutes, Actinobacteria, Bacteroidetes, and Fusobacteria [73]. In low quality samples were detected Prevotella, and Anaerococcus [80].…”
Section: Seminal Microbiota Dysbiosismentioning
confidence: 99%
“…Both infertile and healthy patients seminal fluids show the presence of microbial bacteria, and in the seminal fluids were detected Enterococcus faecalis, Escherichia coli, Streptococcus agalactiae, Ureaplasma urealyticum species [72] (Table 2). Recently, many studies found a sperm bacterial seminal fluid composition characterized mainly by the same bacterial phyla both in healthy donors and azoospermic patients [73]. The low quality sperm morphology patients presented an augmented abundance of Ureaplasma, Enterococcus, Mycoplasma, and Prevotella, in opposition to healthy, which showed a major presence of Lactobacillus [74].…”
Section: Microbial Colonization In Malementioning
confidence: 99%
See 1 more Smart Citation